Reduction of magnetovariational data from arbitrary to geomagnetic reference system - B. T. Ladanivskyy (Ukrainian Antarctic Journal, 2013)
The algorithm for reduction of magnetovariational data acquired in a arbitrary reference system to the geomagnetic one is described. Such a reduction is needed if, for some reason, it is impossible to set  sensors correctly for data acquisition. The algorithm is based on spherical trigonometry formulas.